Implementation of Shariah Governance in the Charitable Sector: Challenges and Importance from an Islamic Perspective - Nik Abdul Rahim, Nik Abdul Ghani; Muhammad Nazir, Alias; Mubarak, S Gh O Alazemi; Mohd Sham, Kamis (Pakistan Journal of Life and Social Sciences, 2024)
The study investigates the implementation of Shariah governance in the charitable sector from an Islamic perspective, emphasizing its significance, challenges, and integration with modern governance practices. The research aims to develop a comprehensive Shariah governance framework that enhances the effectiveness and credibility of Islamic charitable organizations. Utilizing a qualitative methodology, the study conducts content, comparative, and data analyses of primary and secondary sources related to Shariah and corporate governance. The findings highlight the critical role of Shariah governance in ensuring compliance with Islamic principles, enhancing trust, and addressing unique risks faced by Islamic charitable organizations. However, challenges such as the absence of standardized frameworks, a shortage of qualified professionals, and issues in transparency and accountability are identified. The research demonstrates that integrating Shariah governance with modern practices is feasible and advantageous, necessitating a multifaceted approach. The study concludes that effective Shariah governance is vital for the success and sustainability of Islamic charitable organizations. By addressing existing challenges and integrating Islamic principles with contemporary practices, these organizations can improve their credibility, efficiency, and impact. The proposed Shariah governance framework incorporates ethical foundations, robust risk management, transparency, and stakeholder engagement, contributing to the long-term success and sustainability of Islamic charitable organizations. This framework serves as a blueprint for aligning organizational activities with Maqasid al-Shariah, promoting sustainable development, and ensuring ethical leadership. The study's implications are significant for practitioners, policymakers, and researchers, offering practical guidance and highlighting the need for tailored regulatory frameworks and continued research in the field of Islamic governance.